Chemical Profiling and Industrial Viability of Neem Seed Oil: A Comprehensive Study for Sustainable Biodiesel Production - Adamu Zubairu Utono; Usman Rufai Fakai; Basiru Muhammad Suru; Zeenat Abdullahi; Aliyu Garba; Aliyu Kangiwa Ibrahim (International Journal of Applied and Scientific Research, 2024)
The study explores the chemical composition of neem seed oil, highlighting its potential for commercial biodiesel production and various industrial applications. The oil, with a liquid state, pale greenish-yellow color, and pleasant odor, yielded 32.1%, surpassing industrially extracted oils like soybean and cottonseed. Factors influencing its composition include seasonal variations, geographical origin, genetic disparities, growth stages, plant segments, and postharvest processing. Despite these, neem seeds meet the required oil content percentage for large-scale industrial biodiesel production. However, challenges like high free fatty acid content and elevated acid values necessitate acid esterification before alkaline transesterification, potentially increasing production costs. The study also highlights the importance of appropriate seed processing practices to optimize oil yield and quality.